Community of Serbian Municipalities as the middle level administrative authority in Kosovo and Metohija in accordance with the Brussels Agreement - Simić Igor (Megatrend Revija, 2017)
In this paper, the author elaborates the legal framework, competencies, and structure of the Community of Serbian Municipalities in accordance with the agreements reached as part of the Brussels negotiations between Belgrade and Pristina. This topic has not so far been elaborated on behalf of the professional public, since the process of establishing the Community of Serbian Municipalities has not commenced yet in its full scale. Still, this topic is of significant importance to the professional and general public due to its practical implications in terms of solving the largest and oldest political and national dispute in our country. The author conducts a detailed analysis of the legal characteristic of the Community of Serbian Municipalities, its contentious competencies, but also the foreseen structure of its bodies in accordance with the reached agreements, with a special emphasis on certain dilemmas arising during a comparative analysis of the legislation and deals reached.